-13w-19=-11w+6+9

Simple and best practice solution for -13w-19=-11w+6+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -13w-19=-11w+6+9 equation:


Simplifying
-13w + -19 = -11w + 6 + 9

Reorder the terms:
-19 + -13w = -11w + 6 + 9

Reorder the terms:
-19 + -13w = 6 + 9 + -11w

Combine like terms: 6 + 9 = 15
-19 + -13w = 15 + -11w

Solving
-19 + -13w = 15 + -11w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '11w' to each side of the equation.
-19 + -13w + 11w = 15 + -11w + 11w

Combine like terms: -13w + 11w = -2w
-19 + -2w = 15 + -11w + 11w

Combine like terms: -11w + 11w = 0
-19 + -2w = 15 + 0
-19 + -2w = 15

Add '19' to each side of the equation.
-19 + 19 + -2w = 15 + 19

Combine like terms: -19 + 19 = 0
0 + -2w = 15 + 19
-2w = 15 + 19

Combine like terms: 15 + 19 = 34
-2w = 34

Divide each side by '-2'.
w = -17

Simplifying
w = -17

See similar equations:

| 20p+20=19p+14 | | y=4x^2-24x+5 | | -16+9m=11m+20 | | 8x-11+(X-2)=-8 | | -6+3y=2y+9 | | tgx=sqrt(7) | | 15+20m=15m | | (7b-2)-3(2b+3)=-2 | | 5+30x+15x=41 | | 2y+2=6x+2 | | -3g=-14+11g | | 70y=23(3y+18) | | -9p+12=-10p | | 9d-13=1d+6d+17 | | 6m^2=24 | | 3+14b-8b=7b+19 | | -56-10x=24 | | f(-8)=9x+5 | | 8-b=-2b | | 9-8t=-9t+4 | | -2j-10=10+8j | | 8-b=2b | | -4+2-4k=10-8k | | -6+y=-2y+9+6y | | 5z+9=1+9z | | 8(2+6b)+1=-376 | | 3c+10=8c | | 7x-2-6b-9=-2 | | -8-3u=-4u | | 44-5x=9-10x | | 7c=9-2c | | -y=-4x |

Equations solver categories